Combined Dietary Anthocyanins, Flavonols, and Stilbenoids Alleviate Inflammatory Bowel Disease Symptoms in Mice - Scarano, Aurelia; Butelli, Eugenio; De Santis, Stefania; Cavalcanti, Elisabetta; Hill, Lionel; De Angelis, Maria; Giovinazzo, Giovanna; Chieppa, Marcello; Martin, Cathie; Santino, Angelo (Frontiers in Nutrition, 2018)
Dietary polyphenols are associated with a wide range of health benefits, protecting against chronic diseases and promoting healthy aging. Dietary polyphenols offer a complementary approach to the treatment of inflammatory bowel diseases (IBD), a group of common chronic intestinal inflammation syndromes for which there is no cure. Tomato is widely consumed but its content of polyphenols is low. We developed a tomato variety, Bronze, enriched in three distinct classes of polyphenols: flavonols, anthocyanins and stilbenoids. Using Bronze tomatoes as a dietary supplement as well as Indigo (high anthocyanins and flavonols), ResTom (high stilbenoids) and wild type tomatoes, we examined the effects of the different polyphenols on the host gut microbiota, inflammatory responses and the symptoms of chronic IBD, in a mouse model. Bronze tomatoes significantly impacted the symptoms of IBD. A similar result was observed using diets supplemented with red grape skin containing flavonols, anthocyanins and stilbenoids, suggesting that effective protection is provided by different classes of polyphenols acting synergistically.